2011
DOI: 10.1017/s1751731110001825
|View full text |Cite
|
Sign up to set email alerts
|

Responses of prolactin and hair growth to selection for age at puberty in Angus cattle

Abstract: A trial was carried out over a 7-year period (1999 to 2005 calf crops) to compare indicators of seasonality in Angus cattle, which were part of a long-term genetic selection experiment. Divergent selection was applied for early ('AGE2') or late ('AGE1') age at puberty (AP) in heifers, and selection lines differed over the 7-year period by 62 days (15% of the mean). The primary measures of seasonality studied in 629 heifer progeny (59 sire groups) were serum concentration of prolactin (PRL), and winter and sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…BaRIcHEllo et al (2010) for canchim breed (0.52). However, the heritability estimated in our study was higher than that mentioned by MoRRIS et al (2011) for hair length, according to REIMann et al ( 2018) hair length is the measure that most closely resembles the evaluation of hair coat scores. This indicated that the estimate is according to the estimates already reported in the literature.…”
Section: Heritabilitycontrasting
confidence: 63%
“…BaRIcHEllo et al (2010) for canchim breed (0.52). However, the heritability estimated in our study was higher than that mentioned by MoRRIS et al (2011) for hair length, according to REIMann et al ( 2018) hair length is the measure that most closely resembles the evaluation of hair coat scores. This indicated that the estimate is according to the estimates already reported in the literature.…”
Section: Heritabilitycontrasting
confidence: 63%
“…An estimate for heritability for the condition of the coat (subjectively scored as shiny, dull, or very dull) in dairy cows was 0.05 (Jørgensen et al, 2010). Estimates of heritability for hair weight and length in Angus cattle were 0.21 and 0.09, respectively (Morris et al, 2011). Maia et al (2009) reported an estimate of heritability for the effective thermal conductivity of the coat as 0.18.…”
Section: Estimates Of Genetic Effectsmentioning
confidence: 99%
“…Traits of interest could include the age at puberty and heifer pregnancy rate. These candidate traits are measured before calving-related trait and have a greater heritability than traditional reproductive traits captured after calving (Morris et al, 2000(Morris et al, , 2011. Additionally, phenotypic and genetic correlations between heifer traits and subsequent fertility suggest that heifers that calve early have better fertility as cows (Pryce et al, 2007;Tiezzi et al, 2012), indicating that selection for heifer fertility traits could result in better cow fertility.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the onset of puberty reported here is comparable with changes in the onset of puberty reported previously when undertaking single trait section. For example, in a long-term study focused on direct genetic selection for earlier puberty, over 7-yr of single selection puberty was shifted by 62 d (Morris and Amyes, 2005;Morris et al, 2011). This large shift SCR system heat refer to the automated monitoring of estrus events using the SCR Heatime HR system (SCR Engineers Ltd., Netanya, Israel), which included the collar-mounted Heatime sensor.…”
mentioning
confidence: 99%